2019
DOI: 10.1016/j.rbmo.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and appraisal of (inter)national recurrent pregnancy loss guidelines

Abstract: is a 23-year-old medical student, who is combining research with his medical internship. His intention is to become a dedicated gynaecologist. He has already carried out several studies on recurrent pregnancy loss (RPL) and will be investigating RPL as a future PhD student.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 17 publications
(15 reference statements)
3
43
0
3
Order By: Relevance
“…There were many pathogeneses of RPL, including chromosomal abnormalities, autoimmune diseases, anti-phospholipid antibodies, endocrinological abnormalities, thrombophilia disorders and uterine abnormalities. Nearly half of these pregnancy loss reasons need to be explored as well as their psychological and psychiatric effects [2,17]. Women with RPL commonly develop post-traumatic stress disorder, anxiety, depression and other negative psychological problems after pregnancy losses [18].…”
Section: Discussionmentioning
confidence: 99%
“…There were many pathogeneses of RPL, including chromosomal abnormalities, autoimmune diseases, anti-phospholipid antibodies, endocrinological abnormalities, thrombophilia disorders and uterine abnormalities. Nearly half of these pregnancy loss reasons need to be explored as well as their psychological and psychiatric effects [2,17]. Women with RPL commonly develop post-traumatic stress disorder, anxiety, depression and other negative psychological problems after pregnancy losses [18].…”
Section: Discussionmentioning
confidence: 99%
“…There have been many reports on the pathogeneses of RPL, including chromosomal abnormalities, autoimmune diseases, antiphospholipid antibodies, endocrinological abnormalities, thrombophilia disorders and uterine abnormalities [1][2][3]. Nearly half of the aforementioned reasons for pregnancy loss should be explored along with their psychological and psychiatric effects [2,17]. RPL has a remarkable emotional and psychological in uence on women of child-bearing age and their families [2].…”
Section: Discussionmentioning
confidence: 99%
“…These included high priority health topics such as induction of labor [26], planned cesarean Sect. [27], recurrent pregnancy loss [28], packed red cells versus whole blood transfusion for severe pregnancy-related anemia and obstetric bleeding [29], gestational diabetes mellitus [30][31][32], and bladder pain syndrome/interstitial cystitis [33]. These studies identified several gaps, including differences, discrepancies, lack of evidence-base, and inconsistencies in some clinical recommendations among the CPGs; in addition, a few commonalities and similarities in some recommendations with advice to improve these variabilities were observed in CPGs [26][27][28][29][30][31][32][33].…”
Section: Domain 6 Editorial Independencementioning
confidence: 99%